Formulasi dan Uji Karakteristik Sediaan Gel Ekstrak Etanol Umbi Hati Tanah (Angiopteris evecta) - Rezqi handayani; Nurul Qamariah (JURNAL FARMASI DAN MAKANAN, 2023)
Gel is a semisolid topical preparation that provides a cool sensation, easy to clean easy to spread, and has good absorption on the skin. Hati Tanah tuber (Angiopteris evecta) contain Flavonoids, Tannins, and Saponins compounds that act as antibacterials. This study aims to determine whether the ethanol extract of Hati Tanah tuber can be formulated into an anti-acne gel preparation and whether the physical properties of the gel preparation meet the physical standards. The method used in this study was experiment by making gel preparations of ethanol extract of Hati Tanah tuber with variations in extract concentrations of 0%, 0,5%, 1%, and 5% and testing the physical properties of organoleptic, homogeneity, adhesion, dispersion, and pH. The results obtained showed that the gel preparation formulation add with ethanol extract of Hati Tanah tuber had a distinctive smell and color from ethanol extract of Hati Tanah tuber. The physical properties of gel preparations of ethanol extracts of Hati Tanah tuber, namely F1, F2, and F3 in the adhesion test meet the requirements, in the homogeneity test only F2 meets the requirements. While in the dispersion test, only F1 meets the requirements, and in the pH test only F2 and F3 have pH values that meet the requirements.